Unleashing Competitive Edge: The Role of Entrepreneurial Marketing and E-Commerce in Fashion SMEs with Religiosity as a Key Moderator - Saisaria Mandasari, IA Cynthia; Wardana, I Made; Ekawati, Ni Wayan; Setiawan, Putu Yudi (Universitas Brawijaya, Indonesia, 2025)
Small and Medium Enterprises (SMEs) are essential to Indonesia's economy, particularly in Bali Province, where Denpasar City is a key commercial center. This study aims to analyze the role of competitive advantage in mediating the effects of entrepreneurial marketing and e-commerce on the performance of fashion SMEs in Denpasar, with religiosity as a moderator. Using a sample of 134 fashion SMEs, data were collected through questionnaires and analyzed with SmartPLS. The findings show that competitive advantage partially mediates the impact of entrepreneurial marketing and e-commerce on business performance. Additionally, religiosity strengthens the relationship between entrepreneurial marketing and business performance, enhancing consumer trust and ethical practices. This study highlights the significance of integrating religious values into business strategies and the importance of leveraging competitive advantages to improve SME performance. This study offers a novel perspective by integrating religiosity into the entrepreneurial marketing and e-commerce framework, highlighting its moderating role in SME performance. It provides valuable insights for fashion SMEs, emphasizing the strategic importance of aligning business practices with cultural and religious values to foster trust and enhance competitive advantage.